Research on the Implementation of Active Filtering and Reactive Compensation Functions with Grid-connected Inverter - LIU Cong; DAI Ke; ZHANG Shuquan; DUAN Kewei; KANG Yong (Kongzhi Yu Xinxi Jishu)
It researches on the implementation of active filtering and reactive compensation with grid-connected inverter in distributed generation system, and proposes a solution based on load current detection. The detected three phase load currents are transformed to the synchronous coordinate frame through abc/dq transformation, the harmonic and reactive components are extracted by a high-pass or low-pass filter from the d-axis and q-axis components. Then the output current references of the inverter are obtained by synthesizing the extracted currents with the fundamental active current. Output current control is realized by PI+RP compound control algorithm, which ensures the accurate and quick following to the reference. Simulation results show that the inverter could compensate reactive and harmonic currents and transfer the active power at the mean time, which is helpful to power quality improvement.